Keanekaragaman Biota Tanah pada Kebun Kakao di Desa Parenring Kecamatan Lilirilau Kabupaten Soppeng: Diversity of Soil Biota in Cocoa Farms in Parenring Village, Lilirilau District, Soppeng Regency - Lias, Syamsul Arifin; Rhamadani, Naurha; Jayadi, Muh. (Universitas Hasanuddin, 2023)
This study aims to determine the diversity of soil fauna based on the landscape and soil depth in the cocoa plantation in Parenring Village, Lilirilau District, Soppeng Regency. This research was conducted from October 2020 to January 2021 located on a cocoa plantation in Parenring Village, Lilirilau District, Soppeng Regency. This research was conducted by taking soil samples using the Systematic Sampling (SYS) method, using monolithic soil sampling and disturbed soil samples. The observation of soil biota, hand sorting and microscopy were used. Based on the research results, soil samples in the back area had the highest soil biota diversity (H' = 1.32), followed by the valley area (H' = 1.29) and the middle area (H' = 1.18). Soil biota diversity is included in the medium criteria.